2004
DOI: 10.1002/anie.200352534
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Enantioselective Catalyzed Carbonyl‐ and Imino‐Ene Reactions using Copper Bis(Oxazoline) Zeolite Y

Abstract: The current high demand in the pharmaceuticals industry for efficient and economical routes to enantiomerically pure ahydroxy and a-amino carbonyl compounds has focused interest on carbonyl-ene and imino-ene reactions as a potential source of these compounds.[1] Homogeneously catalyzed carbonyl-ene reactions have been reported using a chiral methyl-aluminum-binaphthol complex, [2] but the scope of this catalyst was very limited. Subsequently, the scope of the reaction was widened to the use of 1,1-disubstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…31,[36][37][38][39] CuCl 2 , Cu(NO 3 ) 2 , or Cu(OTf) 2 was used as the copper source. For each Cu(II) source, copper ions were ion-exchanged into the zeolite Y with concentrations corresponding to 0.5, 1, 2, or 4 copper atoms per unit cell (UC) of zeolite Y.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,[36][37][38][39] CuCl 2 , Cu(NO 3 ) 2 , or Cu(OTf) 2 was used as the copper source. For each Cu(II) source, copper ions were ion-exchanged into the zeolite Y with concentrations corresponding to 0.5, 1, 2, or 4 copper atoms per unit cell (UC) of zeolite Y.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] In most cases, the aim is to improve the separation of the catalyst from the products or the selectivity of a catalytic reaction. A zeolite supercage can also be seen as a protective structure around the active center of the catalyst, similar to the protein mantle surrounding the active site of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent thermal treatment would then convert the copper counter anion to a stable form that would bind the copper sites firmly to the support. A similar idea had in fact already been described by Hutchings and coworkers [22,[32][33][34] for Cu-exchanged zeolites and mesoporous materials, using the thermal treatment of copper(II) acetate at 550ºC, followed by treatment with bis(oxazoline) ligands. Nonetheless, in our hands it was not possible to prepare stable catalysts following the same process with our Al-MCM41 supports.…”
Section: Introductionmentioning
confidence: 75%
“…[31][32][33] Complex 1 was also examined for comparison purposes. [34][35][36] The results, given in Table 2, showed that the ee values increased significantly (from 57.5 to 79.5%) with linkage length. Heterogeneous catalysts 4a-e gave much higher ee values than complex 1 under the same conditions.…”
Section: Methodsmentioning
confidence: 96%